Trapped in the postdoctoral void: Lack of postdoctoral opportunities in New Zealand forces emerging researchers to exit science or seek employment overseas - Massaro, Melanie; Yogeeswaran, Krithika; Black, Amanda (New Zealand Science Review, 2012)
​For the recent conference ‘Do emerging scientists have a future in New Zealand’ organised by the New Zealand Association of Scientists (NZAS) on 16 April 2012, we presented a talk entitled ‘Trapped in the postdoctoral void’ to highlight the plight that faces most PhD graduates in New Zealand. The conference was organised in response to an open letter we drafted to the Ministry of Science and Innovation in September 2011 to voice our concern over funding changes that led to the reallocation of resources from the discontinued Foundation for Research, Science and Technology Postdoctoral Fellowship scheme to the Rutherford Discovery Fellowships. It was signed by 560 New Zealand researchers and catalysed a national dialogue on what the future holds for emerging researchers in New Zealand. Following this meeting, we were invited to write an article to express our concerns about the current New Zealand science system and suggest ways to improve the situation. While our concerns and suggestions are strongly relevant to the natural sciences, many apply to broader academia as well.